2020
DOI: 10.1002/ece3.6761
|View full text |Cite
|
Sign up to set email alerts
|

Biocultural diversity of common walnut (Juglans regia L.) and sweet chestnut (Castanea sativa Mill.) across Eurasia

Abstract: A biocultural diversity approach integrates plant biology and germplasm dispersal processes with human cultural diversity. An increasing number of studies have identified cultural factors and ethnolinguistic barriers as the main drivers of the genetic diversity in crop plants. Little is known about how anthropogenic processes have affected the evolution of tree crops over the entire time scale of their interaction with humans. In Asia and the Mediterranean, common walnut ( Juglans regia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 93 publications
0
17
1
Order By: Relevance
“…On the other hand, the introduction of walnut to its new habitats may be dispersed easier by similarities in human language over large geographic areas. This may lead to the genetic homogenization of different populations known as the human role in walnut evolution by merging the plant biology and germplasm dispersal processes data with human cultural and linguistic diversity [54].…”
Section: Ssr Polymorphismmentioning
confidence: 99%
“…On the other hand, the introduction of walnut to its new habitats may be dispersed easier by similarities in human language over large geographic areas. This may lead to the genetic homogenization of different populations known as the human role in walnut evolution by merging the plant biology and germplasm dispersal processes data with human cultural and linguistic diversity [54].…”
Section: Ssr Polymorphismmentioning
confidence: 99%
“…A combined study of ethnolinguistics and genetics suggested a spread of Juglans from the Early Bronze Age, driven by Greek, Roman and Persian expansion/trading (Pollegioni et al 2020). The persistent presence of Juglans pollen from around 2,000 cal yr bp in AM18-5 would be consistent with a Roman expansion of walnut on Cyprus (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…A Bronze Age to Roman period spread of Juglans has been proposed from palynological, ethnolinguistic and genetic studies (Bottema 1980(Bottema , 2000Eastwood et al 1998;Pollegioni et al 2017Pollegioni et al , 2020. Genetics show refugia in southern Europe and Anatolia, which provides a starting point to consider how this important economic species spread (Pollegioni et al 2017(Pollegioni et al , 2020. In the Levant, pollen…”
Section: Discussionmentioning
confidence: 99%
“…It is thus generally agreed that the expansion of the Roman Empire played a decisive role in the spread of these two tree species in Europe and their cultivation, both as fruit trees and for timber production (Conedera et al 2004a;Pollegioni et al 2020). As a result of such a rapid, human-assisted and spatially defined introduction, originating from the territories already conquered by the Romans, both species highlight a relatively low biocultural (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of such a rapid, human-assisted and spatially defined introduction, originating from the territories already conquered by the Romans, both species highlight a relatively low biocultural (i.e. genetic and ethno-linguistic) diversity in Western Europe with respect to the Transcaucasian (both species) and Asian (walnut) areas of Last Glacial Maximum (LGM) refugia (see Mattioni et al 2013Mattioni et al , 2017Fernandez-Lopez et al 2021 for Castanea sativa and Pollegioni et al 2020 for Juglans regia).…”
Section: Introductionmentioning
confidence: 99%